A clinicoanatomical study of thalamic cheiro-oral syndrome - Tominaga, Kayo; Okuda, Bungo; Kamogawa, Kenji; Okamoto, Kensho (Nihon Rōnen Igakkai zasshi, 2006)
We report 6 patients with Cheiro-oral syndrome (COS), with special reference to clinical features and responsible lesions. The time intervals from the onset of symptoms to arrival in our department were less than 24 hours in 3 patients, 2 days in 2, and 5 days in 1. All patients had subjective sensory disturbance involving the unilateral hand and ipsilateral perioral regions, and 4 patients presented with objective sensory disturbance. The body parts of tingling sensation tended to be larger than those of superficial sensory disturbance. Three patients developed motor disturbance including hemiparesis with or without ataxia, clumsiness of fine finger movements, and dysarthria. Magnetic resonance imaging revealed fresh infarctions around the thalamus, including lacunar infarctions in 5 patients and branch atheromatous disease in 1 patient. The lesion sites responsible for COS were ventral posterolateral (VPL) and ventral posteromedial (VPM) nuclei in the thalamus in 4 patients, thalamic pulvinar nucleus and medial geniculate body in 1, thalamic ventroposterior region-internal capsule-corona radiata in 1. Three patients had asymptomatic brain infarctions. Risk factors were hyperlipidemia, hypertension, diabetes mellitus, smoking, arteriosclerosis of the carotid artery, and polycythemia. In the convalescent stage, 5 patients suffered from residual sensory-motor disturbance, whereas 1 patient recovered from COS. COS has been attributed mainly to small infarctions in the thalamic ventroposterior nuclei. However, it is suggested that damage to ascending sensory fibers projecting to the thalamic VPL and VPM nuclei can cause COS. Because initial symptoms of COS are apt to be overlooked, early diagnosis and treatment are necessary to avoid residual sensory-motor disturbance.